A Comparative study between Decompressive Craniectomy with Multidural Stabs and Craniotomy with Durotomy in Acute Subdural Hematoma - Hoque, Saiful; Sarker, Asit Chandra; Khan, Uzzal Kumer Sadhu; Morshed, Md Mahamudul Haq; Roy, Titas; Jahan, Suborna; Uddin, Md Nasir; Rashid, Mamunur (Bangladesh Journal of Neurosurgery, 2021)
Introduction: An acute subdural hematoma (SDH) is one of the most lethal of all head injuries. A good number of patients are encountered in Dhaka medical college and hospital with acute subdural hematoma. There are many modalities for the treatment of acute subdural hematoma, such as decompressive craniectomy with multidural stabs, craniotomy with durotomy. This comparative study was carried -out in the Department of Neurosurgery, Dhaka Medical College and Hospital, Dhaka, during Jan 2016 – Dec 2017, to compare the effect of the decompressive craniectomy with multidural stabs and craniotomy with durotomy in respect to the post operative GCS and GOS. As well as to assess and compare the post operative complications. The type of the study is prospective randomized controlled clinical trial. Materials and Methods: For this purpose, a total of 56 patients of both sex and any age with acute subdural hematoma attended in the above hospital were included in this study. Among them 28 patients underwent decompressive craniectomy with multidural stabs and rest 28 underwent craniotomy with durotomy. Data were collected and analyzed by different variables like age, sex, GCS on admission, GCS on 7th POD, GOS at one month and some complication like operative recurrence, seizure and mortality. Patients or attendants who refuse interview, who managed conservatively and patient who didn’t give consent, patients having severe respiratory distress and or shock, who came after 24 hours of trauma and who had no history of trauma were excluded from the study. Results: The following observations and results were obtained in this study. Nearly two third (63.0%) patients of DC MDS group and 18 (64.3%) in CT DT group age belonged to 21 to 40 years. Most (85.7%) of the patients of DC MDS group and 22 (78.6%) in CT DT group were male. Almost a half (46.4%) patient of DC MDS group and 12 (42.8%) patients of CT DT group GCS on admission belonged to 4 to 8 scale. The differences between two groups were not significant (p>0.05). Nearly a half (46.4%) patient of DC MDS group and 6 (21.4%) patients of CT DT group GCS on 7th POD belonged to 9 to 12 scale. Mortality observed almost one third (32.1%) and 12 (42.9%) in patients of DC MDS group and CT DT group respectively. Regarding the GOS at one month follow up, it was observed 12 (42.9%) patients of DC MDS group and 2 (7.1%) patients of CT DT group had good recovery. About the relation between GCS (on admission) with GOS at one month, we saw that 10(37.7%) patient. GCS was ≥8 where GOS was 4+5 and compare to CT with DT group 9 (32.1%) patients. The difference was statistically significant (p<0.05) and GCS (7th POD) with GOS, it was seen 15 (53.3%) patients GCS was e”8 where GOS was 4+5 and compare to CT with DT group 9 (32.1%) patients. About the complications 4 (14.3%) patients of DC MDS group had both surgical recurrence and seizures. 12 (42.9%) patients of CT DT group had seizures and 11 (39.3%) patients had surgical recurrence. Conclusion: Though mortality between these two groups was not significant, GCS on 7th POD and GOS on 30th POD were significantly better in decompressive craniectomy with multidural stabs group and operative recurrence and seizure was less in decompressive craniectomy with multidural stabs group and was statistically significant. Bang. J Neurosurgery 2021; 10(2): 192-200